Characteristics of nutrients and heavy metals and potential influence of their benthic fluxes in the Pearl River Estuary, South China. (June 2022) - Zhang, Ling; Ni, Zhixin; Li, Jinlong; Shang, Bowen; Wu, Yunchao; Lin, Jizhen; Huang, Xiaoping
Abstract: Nutrient and heavy metal concentrations in porewater/overlying water and their benthic fluxes were investigated to study their accumulation and transport at the sediment−water interface and the influences of sediment in the Pearl River Estuary, China. Results revealed that distribution of nutrients and metals reflected the effects of terrestrial inputs and some physicochemical processes. Benthic fluxes also suggested that nutrients and heavy metals Pb, Zn and Cd diffused from sediment to overlying water, but not for As, Co, Cr, Fe, Mn and Ni. Exchange capacities showed that 10 6 –10 8 mol nutrients and 10 5 –10 7 g Pb, Zn and Cd released from sediment to overlying water annually, indicating their potential ecological threat. However, 10 5 –10 9 g metals As, Co, Cr, Fe, Mn and Ni were deposited annually, which may reduce the pollution pressure caused by anthropogenic activities. This study will provide references for the potential influence of benthic fluxes on estuarine environment globally. Highlights: Nutrient/metal distribution reflected terrestrial inputs and physicochemical process. 10 6 –10 8 mol nutrients and 10 5 –10 7 g Pb, Zn, Cd released from sediment in a year. 10 5 –10 9 g As, Co, Cr, Fe, Mn, Ni were deposited from overlying water in a year. Sedimentary nutrients and Pb, Zn, Cd suggested a potential threat to environment. Sediment is ecologically significant as pollutant deposition and source in the PRE.